2013
DOI: 10.1002/adfm.201203015
|View full text |Cite
|
Sign up to set email alerts
|

Magnetomechanical Four‐State Memory

Abstract: With current non-volatile memory technology approaching intrinsic storage density limits, new data storage technologies are under development. Probe-based storage systems provide alternatives to conventional mass storage technologies. Ni-Mn-Ga, a ferromagnetic shape memory alloy (FSMA), is proposed as a medium for multi-bit storage using scanning probe microscopy (SPM) techniques. Local modifications of the magnetic stray field were achieved using nanoindentation. Magnetic poles collect within the indentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…[10][11][12] While reducing the sample size increases blocking stress up to 10 MPa, 13 fewer twinning dislocations-which are the vehicles that transport preferentially aligned martensite variants-are present at small length scales. As a result, higher stresses may be required to initiate twin boundary movement in smaller samples, competing with the fundamental actuating functionality of Ni-Mn-Ga. 14 Nanoindentation, either alone or in combination with scanning probe microscopy techniques such as atomic force microscopy (AFM) or magnetic force microscopy (MFM), has previously been applied to Ni-Mn-Ga to (i) evaluate the role of twinning during nanoscale deformations, 15,16 (ii) probe the local elastic properties of twin boundaries, 17 (iii) manipulate the local stray magnetic field for memory applications, 18 (iv) facilitate martensitic transformation for magnetocaloric applications, 19 and (v) demonstrate lattice softening in pre-martensitic Ni-Mn-Ga. 20 Of particular relevance to the current work, Ganor and Shilo showed that nanoindentation techniques can be used to resolve differences in reduced elastic modulus of martensitic Ni-Mn-Ga across 90 twin boundaries. 21 In that work, the authors identified anisotropy in the reduced elastic modulus of Ni-Mn-Ga, where the modulus measured perpendicular to the c-axis (i.e., for martensite variants exhibiting an in-plane c-axis orientation) was significantly less than that measured parallel to a)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] While reducing the sample size increases blocking stress up to 10 MPa, 13 fewer twinning dislocations-which are the vehicles that transport preferentially aligned martensite variants-are present at small length scales. As a result, higher stresses may be required to initiate twin boundary movement in smaller samples, competing with the fundamental actuating functionality of Ni-Mn-Ga. 14 Nanoindentation, either alone or in combination with scanning probe microscopy techniques such as atomic force microscopy (AFM) or magnetic force microscopy (MFM), has previously been applied to Ni-Mn-Ga to (i) evaluate the role of twinning during nanoscale deformations, 15,16 (ii) probe the local elastic properties of twin boundaries, 17 (iii) manipulate the local stray magnetic field for memory applications, 18 (iv) facilitate martensitic transformation for magnetocaloric applications, 19 and (v) demonstrate lattice softening in pre-martensitic Ni-Mn-Ga. 20 Of particular relevance to the current work, Ganor and Shilo showed that nanoindentation techniques can be used to resolve differences in reduced elastic modulus of martensitic Ni-Mn-Ga across 90 twin boundaries. 21 In that work, the authors identified anisotropy in the reduced elastic modulus of Ni-Mn-Ga, where the modulus measured perpendicular to the c-axis (i.e., for martensite variants exhibiting an in-plane c-axis orientation) was significantly less than that measured parallel to a)…”
Section: Introductionmentioning
confidence: 99%
“…AFM and MFM are a powerful combination, as together they can reveal changes in the twin structure and magnetic axis orientation at the nanoscale in response to applied thermomechanical stresses. 15,16,18,23 MFM is particularly useful and instructive in the case of FSMAs such as Ni-Mn-Ga, as it provides the ability to readily identify twins and the orientation of the easy magnetization axis (c-axis) at the nanoscale, which is not possible in the case of non-ferromagnetic shape memory alloys such as NiTi (nitinol).…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory properties of Ni-Mn-Ga make it an ideal candidate for applications including micro-fluid pumps, energy harvesting, and memory devices [7][8][9][10][11]. For these uses, long fatigue life and fracture resistance are required when FSMAs are actuated thousands or even millions of times and failure caused by nucleation and propagation of cracks must be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…In these materials, the magnetic moment is strongly coupled to the crystal lattice, and therefore the rotation of the magnetic moments by an external driving force can lead to a consequent rearrangement of crystal lattice in the form of twin reorientation. As a result, strong coupling between magnetic moments and crystallographic twin orientations can give rise to many interesting effects such as large magnetic-field-induced strains and memory effects in resistivity and magnetization, with potential applications in smart actuators and information storage [4][5][6][7]. Therefore, from both fundamental and technological viewpoints, it is of utmost importance to be able to quantitatively determine and model both magnetic moment rotation and twin reorientation, which can occur simultaneously under the application of magnetic fields.…”
Section: Introductionmentioning
confidence: 99%